Cover Feature: Ruthenium Complexes Bearing Bis‐N‐heterocyclic Carbene Donors in TiO2 Sensitization for Dye‐Sensitized Solar Cells (Eur. J. Inorg. Chem. 35/2022). Issue 35 (24th November 2022) - Jain, Nimisha; Mary, Angelina; Dalal, Pooja Munish; Sakla, Rahul; Jose, D. Amilan; Jain, Mukesh; Naziruddin, Abbas Raja
Abstract : The Cover Feature shows photoexcitation of a ruthenium (II) complex, [Ru(C^C)(tpy 4′−COOH )(NCS)](PF6 ), bearing bis ‐N‐heterocyclic carbene ligands bound to a TiO2 surface via a carboxylic acid anchor. These photosensitizers can harvest sunlight of wavelength up to 800 nm in a Dye‐Sensitized Solar Cell setup. More information can be found in the Research Article by A. R. Naziruddin and co‐workers .